OPPORTUNITY AND CHALLENGES MSME FOR THE PAST 6 YEARS: A SYSTEMATIC REVIEW - Vivi Usmayanti; Nanda Nur Sofyana (TECHNOBIZ : International Journal of Business, 2022)
This paper presents a systematic review of MSME development from 2016 to 2021. MSME is the established topic that plays an essential role in economic stability and sustainability in a country. This topic is extended more in various methods, topics, and clusters. This study has reviewed 41 papers and provided four main findings. Firstly, in terms of theory, entrepreneurship theory, internationalization entrepreneurship theory, and technology-organization-environment framework are the theories and approaches commonly used in MSMEs topic. Secondly, literature review and survey dominate the methodology of MSMEs study. Third, the country's origin to conduct the research is not only in Asia and Africa but also in Serbia (Europe). Thirdly, the business sector of MSME is various, but food and Fashion have the most percentage amongst the other business. The last, based on social network analysis, five clusters connect each node in the issues. The study suggests future research agenda such as technological adaptation in MSME to improve their marketing strategy, especially post-Covid-19. These would contribute to establishing the field that can support MSME owners in the future.Keywords: MSME, social network analysis, systematic review, visualization